Peran Otonomi Desa dalam Mendorong Kemandirian Desa di Indonesia - Putu Eka Pitriyantini (Universitas Tabanan, 2026)
Desa autonomy constitutes a manifestation of state recognition of customary law communities as mandated in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. This study examines the juridical basis of village government authority in managing village affairs and its implications for achieving village self-reliance within the framework of the Unitary State of the Republic of Indonesia. Using a normative juridical approach, this research analyzes statutory regulations, particularly Law Number 6 of 2014 on Villages and Law Number 23 of 2014 on Regional Government. The findings indicate that village authority is not merely administrative in nature, but reflects original autonomy rooted in traditional rights and local customs. Such autonomy provides space for villages to independently administer governance, development, and community empowerment through the optimization of local resources, including the management of Village-Owned Enterprises (BUMDes). However, the implementation of Desa remains within the national governance system, requiring alignment with central and regional government policies. Therefore, village autonomy holds strategic significance as a constitutional instrument in strengthening village self-reliance while maintaining the integrity of Indonesia’s state system